Allergen‐specific immunotherapy for patients with atopic dermatitis sensitized to animal dander. Issue 2 (12th March 2020) - Chu, Howard; Park, Kyung Hee; Kim, Su Min; Lee, Jae‐Hyun; Park, Jung‐Won; Lee, Kwang Hoon; Park, Chang Ook
Abstract: Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease, and AD patients are commonly sensitized to house dust mite (HDM). Of the several treatment options available, allergen‐specific immunotherapy (AIT) has been recognized as an effective treatment modality that is directed toward the immunoglobulin E (IgE)‐mediated nature of AD, and subcutaneous administration using HDM is most commonly used for AIT in AD. For patients sensitized to animal (dog or cat) dander, the treatment may not be easy, especially when avoiding the allergen is not possible. Methods: This study enrolled patients with AD who were sensitized to cat and/or dog dander and underwent AIT (n = 19). Patients' medical information was obtained, including past treatment history, treatment duration of AIT, and the progress of treatment. Also, the specific IgE levels and IgG4 levels were measured before and after AIT. Results: A total of 19 patients with AD underwent AIT using cat and/or dog dander. The patients consisted of 4 males and 15 females with an average age of 31.74 ± 9.71. Only two patients had AD only, and the other 17 patients had one or more concomitant allergic diseases, such as allergic rhinitis, allergic asthma, or allergic conjunctivitis. Seven patients were not sensitized to HDMs and only sensitized to cat and/or dog dander. The duration of AIT ranged from 2 to 58 months. The symptoms of 17 patients were well‐controlled, requiring only topical treatment and/or oral antihistamines. One patient required systemic cyclosporine, but only of low dose (25 mg/day). The specific IgE levels were decreased ( P = .005) and IgG4 levels showed the tendency of increasing after AIT. No adverse events were observed in these patients. Conclusion: Although a larger number of patients for a longer follow‐up period are needed to precisely assess the treatment efficacy, AIT using cat and/or dog dander may be an effective treatment option for AD patients, especially for severe AD patients with other respiratory allergic comorbidities who cannot completely avoid the exposure to animal dander. Abstract : As the sensitization to animal dander, predominantly cat and dog dander, constitutes a significant portion in patients with atopic dermatitis (AD), treatment modalities directed toward the desensitization of these allergens should also be available. While allergen‐specific immunotherapy using cat and/or dog dander is performed in patients with respiratory allergic diseases, there has been no report for AD, and in this study, we found that it was effective in AD as well.